Public transportation (bus) simulation development - Muhammad Haziq Mohammed Shahrin (Nanyang Technological University, 2020)
This project aims to utilise the traffic simulation software, PTV VISSIM to model out public transportation, specifically buses and to study the bus dispatching system used. As congestion becomes an increasingly common encounter for road users, more emphasis is placed on the public transportation system in Singapore. Moreover, even the government is encouraging people to commute to work via public transport and to leave their private vehicles home. It is thus important to review the bus dispatching system used by buses to understand it and see where improvements can be made. As such, PTV VISSIM will be used to first build a network of roads, as realistically as possible, and incorporate the public transport system as well. The many variables in modelling out the network will be calibrated as realistic as possible to ensure the results will largely mimic that of what is happening on the roads. Once the network model is built, simulations will be run to study the effect of traffic volume on the bus dispatching system currently at use. This will be done by varying the traffic volume in the simulations in stages. Different bus frequencies will also be used to reflect the different flow of buses throughout the day, based on the current dispatching method. The travel time of the buses to complete one cycle will be collected. Through this result, statistical analysis will be done. The results will be studied before recommendations or improvements be suggested to ensure a more efficient bus scheduling system. At the end, a conclusion will be made, and possible future works will be discussed.